Perceraian dan Perubahan Sosial di Kabupaten Bungo (Studi terhadap Tren Pola Perceraian dari Talak Cerai ke Gugat Cerai) - Hasan, Bakhtiar; Muhammad, Arsa (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2009)
This is a kind of field research with law sociological approximation in order to see clearly the changing tren of divorces pole at Bungos Regency and its factors. From the research, it founded that some divorces has had changing pole: from divorce with repudiation becomes divorce claim. And most of divorce factors at Bungo is done with motive the husband has not been responsible anymore, there is no harmony, violence at home, economic factor and husband as prisoner. But the most dominant factor is caused irresponsible husband.